Prison farm inmates' reformation and rehabilitation : the Nigerian experience - Uddin, Irenonsen Oyaimare (Array, 2019)
The main objective of this study was to assess farm management activities of prison farms in Nigeria. The study adopted a survey design. Most implemented programs in prison farms included crop production. Inmates preferred rice farming because it is a staple food with a readily available market to sell and make profit. There were no provisions made by the management of the prison farms visited to reach out to prisoners upon release. Agricultural activities that could increase inmates’ chances of gainful employment when released and channel energy and thoughts towards positive things motivated them to effectively participate in farm operations. To enhance inmates’ skills acquisition in agricultural vocations, more efforts should be made by the management of Nigerian prisons service to sustain fully implemented agricultural programswhile attempts are made to fully implement other agricultural programs, especially in the areas of animal husbandry.